Lethality Assay of Radiopharmaceutical bis-Thiosemicarbazones Using Brine Shrimp (Artemia salina) Test: Toxicity of bis-thiosemicarbazones - Aytak Novinrooz,; Sahar Sadraee,; Amir Reza Jalilian,; Marzieh Heydarieh,; Mehdi Akhlaghi, (Iranian Journal of Pharmaceutical Sciences, 2012)
In the present study, aqueous solutions of some copper-complexing ligands were screened for their cytotoxicity using brine shrimp lethality test. Among the ligands tested, diacetyl-bis(N4- methylthiosemicarbazones) (ATSM) proved to be the most safe and non-toxic compound (2% lethality at 10 ppm), while pyruvaldehyde Bis(N4-methyl)thiosemicarbazone (PTSM) was shown to possess low toxicity (7% lethality at 10 ppm) and glyoxal-bis-thiosemicarbazone (GTS) proved to be a toxic compound even at 1 ppm (20% lethality). An interesting structure-toxicity relationship was observed for the ligands based on their water solubility leading to more toxicity which can be related to polysaccharide crustae of the shrimps. Considering the 1-10 ppm to be the maximum possible concentration of the ligands in the final pharmaceutical samples, the safety of these ligands are ATSM>PTSM>GTS.